Acceptance of micro-takaful among B40 in Malaysia: a study on urban B40 - Nur Syakirah, Hashim (2023)
Takaful which is Islamic insurance or Syariah compliance insurance is a protection plan and there are micro-takaful that provided smaller amount of protection specially develop for lower income group people. In this Covid-19 epidemic, micro-takaful is a way to provide a person and his family with financial security against unforeseen tragedies. However, in nowadays situation especially after post-covid with the inflation getting increase, the level of acceptance to the micro-takaful is getting reduce. There are several types of lower income group, and this study will focus on Urban B40 in Malaysia since this group is getting larger and they have more information and also aware on the takaful but what are the factors that may influence them in accepting micro-takaful. Therefore, this study aims to investigate the factors that influence urban B40 in Malaysia on the acceptance of micro-takaful. This study employed descriptive analysis, Pearson correlation, and multiple regression to analyse 519 survey questions. According to the analysis results, it indicated that among Urban B40, peer effect, service quality, risk mitigation and financial literacy are significantly influence with positive direction towards the acceptance of micro-takaful. The risk mitigation is the most important component, which implies that the Urban B40s are worried about their family or heirs. Thus, this important factor has to be taken seriously to accelerate the penetration rate of micro-takaful among the Urban B40, in parallel with the government and takaful provider initiatives.